Effects of a Proteinase Inhibitor from Inga laurina Seeds (ILTI) on Aedes aegypti Larval Development - Ana Jacobowski; Welington Leite; Antolim Martinez Júnior; Eduarda Reis; Lorena Pires; Vitória Silva; Layza Rocha; Eduardo Arruda; Octávio Franco; Marlon Cardoso; Priscila Hiane; Maria Macedo (Journal of Xenobiotics, 2025)
Aedes aegypti (Linnaeus, 1762) is Brazil’s primary vector of epidemiologically significant arboviruses such as yellow fever, dengue, Zika, and chikungunya. Despite using conventional chemical control measures, this species has developed resistance to standard chemical insecticides, prompting the search for natural larvicidal compounds. Plant protease inhibitors offer an insecticidal alternative as the primary digestive enzymes in the midgut of Ae. aegypti are proteases (trypsin and chymotrypsin). Ae. aegypti larvae fed with ILTI, a Kunitz-type trypsin inhibitor derived from Inga laurina seeds, at concentrations between 0.03 mg of protein per mL (mgP/mL) and 0.12 mgP/mL, exhibited delayed larval development, with a lethal concentration (LC50) of 0.095 mgP mL−1 of ILTI for 50% of fourth-instar larvae (L4). The ex vivo assay indicated that ILTI effectively inhibited the activity of larval trypsin, which remained susceptible to the inhibitor. Additionally, molecular modelling and docking studies were conducted to predict the three-dimensional ILTI/enzyme molecular complexes at the atomic level. Therefore, the results demonstrate that ILTI functions as a protease inhibitor in this species, presenting itself as a promising larvicidal tool in the control of Ae. aegypti.